Analysis of growth variations and expression patterns of auxin response factor gene family in Fallopia multiflora under different light qualities - Liu, Wenze; Zhou, Shengwei; Zheng, Yuxin; Hou, Wenchuan; Chu, Leixia; Dong, Ning; Zhang, Ruihang; Wang, Mengping; Gu, Xupeng; Wan, Jie; Liu, Shouhua; Yang, Linlin; et al. (Frontiers in Plant Science, 2025)
Light is one of the most pivotal environmental factors in plant life activities and plays a crucial role in regulating the synthesis of plant secondary metabolites. However, there is no report on the response mechanism of F. multiflora to different light quality treatments. In this study, different light qualities were applied. Physiological characteristics and secondary metabolites of plants, including leaf area, chlorophyll, proline, physcion, emodi, THSG etc., were measured after 20-day light quality treatment. Subsequently, the FmARF gene family was identified and analyzed the expression under the impact of light quality. Results showed that the blue-light treatment group significantly increased the leaf area by 46.19% and chlorophyll content by 7.35%, decreased the plant height by 20.92%, and increased the THSG content in roots by 28.37% and in stems by 27.15%. The yellow-light treatment significantly increased the proline content by 94.47% and the soluble sugar content by 19.03%. The red-light treatment significantly increased the plant height by 83.56%. There are 37 FmARF genes in F. multiflora, which are classified into four sub-families. Whole-genome duplication and segmental duplication are the predominant expansion modes. The promoters are abundant in light and other response elements, and most genes show tissue-specific expression. Correlation prediction analysis revealed that in the stems, the content of stilbene glycoside was significantly negatively correlated with FmARF9 and 30, and free anthraquinone components such as physcion and emodin were significantly negatively correlated with FmARF2, 5 etc. In the roots, the content of stilbene glycoside was significantly negatively correlated with FmARF8, 9, 29, and positively correlated with FmARF17; physcion was negatively correlated with FmARF2, 5 etc., and positively correlated with FmARF8, 9 etc.; emodin was negatively correlated with FmARF2, 5 etc., and positively correlated with FmARF9, 15 etc. This study demonstrates that there are significant differences in the growth and development of F. multiflora under different light quality treatments. The FmARF gene family may mediate light quality regulation and metabolic synthesis pathways. This research provides a theoretical basis for the functional identification of key candidate genes for light regulation and the study of the molecular mechanism of light regulation in F. multiflora.